E-169 Institutional experience from 750 neuroendovascular procedures using transradial approach – a prospective observational study. (4th August 2020) - Almallouhi, E; Al kasab, S; Pai, S; Lena, J; Spiotta, A
Abstract : Background: More evidence is emerging in the last two years regarding the feasibility of using transradial approach (TRA) for most neuroendovascular procedures. In addition, TRA has better safety profile and patient satisfaction compared to the traditional transfemoral approach. In this study, we present our experience in transitioning the 'radial-first' approach over a course of one year. Methods: We prospectively collected demographic and procedural variables of all patients who underwent neuroendovascular procedure using the TRA between starting from March 2019. Exclusion criteria included: 1) known vasoocclusive disease such as Raynaud disease, Takayasu arteritis, or thromboangiitis obliterans; 2) known complex radial or brachiocephalic anatomy such as aberrant right subclavian artery or situs inversus; 3) procedures that require the use of devices that are larger than 8-French. Predefined interim analyses were planned at 500, 750 and 1000 patients. Results: A total of 750 patients included in this analysis (615 underwent cerebral angiogram and 135 underwent an interventional procedure). Mean age was 55.8 (±15.1), 442 (58.9%) were females, and 434 (57.9%) underwent the procedure in outpatient setting. The right radial artery was used in 730 (97.3%) cases, ulnar artery in 16 (2.1%), and left radial artery in 4 (0.5%) cases. A 4/5-French slender sheath was used for cerebral angiograms and a 5/6 or 6/7-French slender sheath was used for interventional procedures. Interventional procedures included flow diversion in 27 cases, 25 cerebral aneurysm primary coiling cases, 17 stent-assisted coiling cases, 11 balloon-assisted coiling cases, 26 tumor and middle meningeal artery (MMA) embolization cases, and 7 mechanical thrombectomy cases. The overall success rate was 94.8% (711/750): 95.4% (587/615) for cerebral angiograms and 91.9% (124/135) for patients who received an intervention. Overall success rate improved from 93.3% in the first 3 months of the study to 98.3% in the last 3 months (P=0.049). Complications related to access sites were seen in 7 (0.9%) patients: 5 patients had forearm hematoma and 2 had prolonged vasospasm/arm pain that resolved with conservative management. Other complications included post-procedural stroke in 2 patients and sent thrombosis in 1 patient. Conclusion: Incorporation of radial-first approach for neuroendovascular procedures is safe and feasible. TRA is associated with learning curve and success rate improved during the study period. Disclosures: E. Almallouhi: None. S. Al kasab: None. S. Pai: None. J. Lena: None. A. Spiotta: 1; C; Penumbra. 2; C; Penumbra, Stryker, Cerenovus, Terumo.